Letter (copy) - Gondra, Angel de
025a-0008-001 Copy Sent by NUS 11 Jan 41 BASQUE DELEGATION, 7/8, Hobart Place, Eaton Square, S.W.1. 8th January, 1941. The Secretary, National Union of Seamen, Connaught Rd. Station, E.16. Dear Sir, You will no doubt recall that when the Basque seamen landed in this country, your Union was good enough to take them under its care. We are very grateful for your help on that occasion, which was equally appreciated by the men concerned, and we are happy to say that they are now making some small contribution to the British war effort by serving abroad the ships which are bringing food and supplies to these shores. We would now like to bring to your notice the case of another of our Basque seamen, Joaquin de Equia, aged thirty-seven, a Captain in the Basque Mercantile Marine. In Bilbao he was in charge of the naval forces of Euzkadi, and was on the best of terms with the British naval units with whom he came in contact on their visits to that port. Capt. Eguia is now in Eire, having escaped from France in a fishing boat after the Armistice, and he is very anxious to obtain permission to come to this country and offer his services to the Mercantile Marine. He has approached the authorities there, and has been told that before a permit can be granted he must present a contract of engagement. On his behalf we have also approached the Passport Control Department of the Foreign Office, and have received a reply to the effect that in the event of arrangements being made in advance for his entry into the Merchant Navy, they would instruct the Permit office to grant the necessary visa. In these circumstances, we should be very gratefil if it should be within your power, if you would be good enough to facilitate the granting of a contract of engagement in favour of Capt. Eguia, in order that we may obtain the permit for him to enter this country. We should, of course, guarantee his maintenance while in this country. yours faithfully, (SIGNED) A. DE GONDRA. Secretary, 292/946/25a/8